Carotid Web (Intimal Fibromuscular Dysplasia) Has High Stroke Recurrence Risk and Is Amenable to Stenting. Issue 11 (November 2017) - Haussen, Diogo C.; Grossberg, Jonathan A.; Bouslama, Mehdi; Pradilla, Gustavo; Belagaje, Samir; Bianchi, Nicolas; Allen, Jason W.; Frankel, Michael; Nogueira, Raul G.
Abstract : Background and Purpose—: Carotid webs have been increasingly recognized as a cause of recurrent stroke, but evidence remains scarce. We aim to report the clinical outcomes and first series of carotid stenting in a cohort of patients with strokes from symptomatic carotid webs. Methods—: Prospective and consecutive data of patients <65 years old with cryptogenic stroke admitted within September 2014 to May 2017. Carotid web was defined by a shelf-like/linear filling defect in the posterior internal carotid artery bulb by computed tomographic angiography. Results—: Twenty-four patients were identified (91.6% strokes/8.4% transient ischemic attacks [TIAs]). Median age was 46 (41–59) years, 61% were female, and 75% were black. Median National Institutes of Health Stroke Scale score was 10.5 (3.0–16.0) and ASPECTS (Alberta Stroke Program Early CT Score) was 8 (7–8). There were no parenchymal hemorrhages, and 96% of patients were independent at 3 months. All webs caused <50% stenosis. In patients with bilateral webs (58%), median ipsilateral web length was larger than contralateral (3.1 [3.0–4.5] mm versus 2.6 [1.85–2.9] mm; P =0.01), respectively. Twenty-nine percent of patients had thrombus superimposed on the symptomatic carotid web. A recurrent stroke/TIA involving the territory of the previously symptomatic web occurred in 7 (32%; 6 strokes/1 TIA) patients: 3 <1 week, 2 <first year, and 3 >1 year of follow-up. Two recurrences occurred on dual antiplatelet therapy, 3 on antiplatelet monotherapy, 1 within 24 hours of thrombolysis, and 1 off antithrombotics. Median follow-up was 12.2 (8.0–18.0) months. Sixteen (66%) patients were stented at a median 12.2 (7.0–18.7) days after stroke with no periprocedural complications. No recurrent strokes/TIAs occurred in stented individuals (median follow-up of 4 [2.4–12.0] months). Conclusions—: Carotid web is associated with high recurrent stroke/TIA risk, despite antithrombotic use, and is amenable to carotid stenting. Abstract : Supplemental Digital Content is available in the text.